Complex Regional Pain Syndrome: Contemporary Diagnostic and Therapeutic Methods - Wójtowicz, Jan; Ujazda, Damian; Głąb, Weronika; Dominiak, Oliwia; Komoń, Aleksandra; Grobelny, Artur (Journal of Education, Health and Sport, 2026)
Complex Regional Pain Syndrome (CRPS) is a chronic condition, most commonly affecting the limbs, characterized by pain disproportionate to the initial injury and various autonomic, sensory, vasomotor, and motor symptoms. CRPS significantly reduces patients' quality of life, and its complex pathophysiology—which involves inflammatory, neurogenic, and autoimmune processes—poses significant diagnostic and therapeutic challenges. This study aims to present and analyze contemporary diagnostic and therapeutic methods used in the management of CRPS, focusing on current scientific knowledge and future perspectives.